Towards a deep experience within Participatory Action Research - Jorge Urdapilleta Carrasco; Fernando Limón Aguirre (Revista Colombiana de Sociología, 2018)
Based on Larrosa’s phenomenological treatment on the value of experience as a source of knowledge as well as the ideas of Antonio Gramsci, Paulo Freire and Orlando Fals Borda, the article presents a systematized proposal for those carrying out Participatory Action Research (par). In this sense, those carrying out par must assume the implications of a socially committed science and the importance of experience as a means of both personal and collective self-knowledge and transformation. In the first place, these transformations spur from the acknolwegment of researchers as vulnerable, sensitive and sensible subjects. In the second place, they are based on the establishment of affective relationships in which the experience sustains the commitment of par as a sociological option. The article proposes that those choosing this option be aware of how their position is influenced by paradigms of instrumental rationality which employ quantification aims to validate knowledge. Faced with this, another option of relational rationality arises, proposing good living and inviting us to understand existence from the historical-collective experience. This aims to cultivate an attitude of openness and affective and spiritual attention with respect to events and establish reciprocal relationships. To develop this attitude, we must assume positions of co-creation, mediation, service, co-fraternization and reconciliation, constantly working within different daily spaces, sacred and intimate, to generate greater confidence, openness and availability on behalf of the collectives. The aim must be more than collecting data or complying with indicators; it must be to experience the emotive and even spiritual scope of our task, given the resonance produced during the coexistence.